Person-organization fit and conflict resolution in the Eye Referral Center - Romualdez, Alfredo Carmelo K. (Animo Repository, 2015)
In the case of the Eye Referral Center, where its goals are incompatible with that of its doctors Beattie (2005) helps provides insight into the difference in perspectives of each group as possible areas where conflict may emanate. Through the application of Person-Organization Fit as discussed by Cable and Judge (1995) and Bozkurt, Kalakan, Ulutas (2011) for which I was able use to understand the differences between complementary and supplementary fit and where goal congruence must be met to achieve Person-Organization fit and how goal incongruences or incompatibilities would inevitably lead to conflict. I have made use of the Levels of Corporate Engagement in Social and Environmental framework by Roman (2007) as it highlights the importance of compliance in meeting the vision of the Eye Referral Center. Using the Two- Dimensional Model of Conflict Behaviour, by Kilman & Thomas (1976), I was able to learn the ways we consciously or unconsciously manage conflict as either through competing, collaborating, compromising, avoiding or accommodating. Buddhodev (2011) has created an adaptation of the Two-Dimensional Conflict Behaviour model in which he was able to suggest particular instances where particular approaches would be most appropriate and effective. The determinants of the approaches were mainly based on the complexity, timeliness and importance of the issue and the power of the groups. I together with the administrator and medical director were able to develop interventions to ensure that our doctors comply with regulatory requirements. After the first set of interventions have been implemented, we have noticed they have improve the doctors compliance however they had also brought about some unforeseen negative activities in the center. We revisited the criteria and were able to meet full compliance with our objectives after the second set of interventions.